Model-Driven Ethical, Social and Environmental Accounting - Ramautar, Vijanti (Proceedings of the 7th International Conference on ICT for Sustainability, 2020)
Ethical, social and environmental accounting is the practice of assessing organisations' performances in sustainability and business ethics topics. The organisations typically publish the results in a sustainability or non-financial report. We aim at offering a novel perspective from which researchers investigate, practitioners apply and policy-makers regulate ethical, social and environmental accounting (ESEA). The large quantity of ESEA methods and tools causes managerial problems, affecting the identity of social enterprises and complicating policy making. We will develop a domain-specific modelling language to specify existing ESEA methods and capture the advantages of model-driven engineering. We will create a repository where method models can be stored. These models contain the data structure and configuration of the methods. We will also develop openESEA, a run-time model interpreter that automatically executes ESEA method models. We will offer features to allow organisations to tailor the methods to their needs, to support model management operations, and to compare existing methods to inform policy makers about their similarities and differences. This project combines expertise in information science and social entrepreneurship with the intention to pave the way to future research avenues in ESEA and, eventually, to profound changes towards a fair and sustainable economy.
Keywords: Développement Durable-Responsabilité Sociale (DD-RS); Ethical; social and environmental accounting (ESEA); Réservé UdeM